PP.04.09: LYSYL OXIDASE OVEREXPRESSION ACCELERATES HYPERTENSIVE CARDIOMYOPATHY. (June 2015) - Galan, M.; Varona, S.; Orriols, M.; Aguiló, S.; De Diego, A.; Navarro, M.A.; Osada, J.; Martinez-González, J.; Rodriguez, C.
Abstract : Objective: Lysyl oxidase (LOX) is a key enzyme in extracellular matrix (ECM) remodelling. Because LOX deficiency is lethal, we have developed a transgenic mouse model to study the impact of LOX overexpression on cardiovascular remodelling. Design and method: A new mouse model that over-expresses human LOX was generated by conventional methods. Transgene expression was determined by real time PCR in 8 different tissues including aorta, heart, kidney, white adipose tissue (WAT), brown adipose tissue, lung, liver and skeletal muscle. We tested the impact of LOX over-expression on cardiovascular remodelling in TgLOX mice and their wild-type (WT) littermates mice after chronic infusion with Ang II (1.4 μg/kg/min) or saline (n = 10 per group). Aortic diameter and cardiac function were evaluated by ultrasonography. Results: The maximum expression of human LOX was found in aorta followed by heart and WAT. Neither the expression of endogenous LOX nor that of LOX-Like (LOXL) isoenzymes was modified by transgene expression in these tissues. Ang II-induced aortic diameter dilation was similar in TgLOX and WT mice after Ang II infusion. However, the mortality rate due to aortic rupture was higher in WT mice (20 %) compared to TgLOX mice (0 %). The quantification of heart function showed that Ang II infusion decreased ejection fraction (EF) and fractional shortening (FS) in TgLOX mice, while they were augmented in WT mice. A stronger hypertrophic response induced by Ang II occurred in TgLOX mice as evidenced by an increased LV mass and left ventricle posterior wall (LVPW) thickness. Accordingly, the left ventricular inner diameter (LVID) was significantly lowered in TgLOX mice. After Ang II infusion, cardiac output, stroke volume and mRNA levels of hypertrophic markers such as ANP and B-HMC remained similar in both, transgenic and WT mice. Finally, LOX overexpression increased the Ang II-induced expression of pro-inflammatory (Emr-1, IL6, Mmp-9) and fibrosis-related (Serpin-1, Col-1a1) markers in cardiac tissue compared with WT mice Conclusions: We have developed a valuable model to improve our knowledge about LOX biology in the cardiovascular system. Our data evidence that LOX over-expression impairs cardiac function under hypertensive conditions.